Invited review: dysregulation of chromatin remodellers in paediatric brain tumours - SMARCB1 and beyond - Johann, Pascal-David (Neuropathology & applied neurobiology, 2020)
Mutations in chromatin remodelling genes occur in approximately 25% of all human tumours (Kadoch et al. Nat Genet 45: 592-601, 2013). The spectrum of alterations is broad and comprises single nucleotide variants, insertion/deletions and more complex structural variations. The single most often affected remodelling complex is the SWI/SNF complex (SWItch/sucrose non-fermentable). In the field of paediatric neuro-oncology, the spectrum of affected genes implicated in epigenetic remodelling is narrower with SMARCB1 and SMARCA4 being the most frequent. The low mutation frequencies in many of the SWI/SNF mutant entities underline the fact that perturbed chromatin remodelling is the most salient factor in tumourigenesis and could thus be a potential therapeutic opportunity. Here, I review the genetic basis of aberrant chromatin remodelling in paediatric brain tumours and discuss their impact on the epigenome in the respective entities, mainly medulloblastomas and rhabdoid tumours.